Pengaruh Custemer Experience dan Kepercayaan Pelanggan Terhadap Kepuasan Pelanggan - Syahyono; Chendy Rachman, Osama (Economic Reviews Journal, 2025)
Customer experience is one of the elements that can increase customer satisfaction. Positive experiences will be remembered by customers and have the potential to increase their loyalty to certain brands. This study aims to analyse the effect of customer experience on customer satisfaction and loyalty. The research was conducted with a quantitative approach using the explanatory method. Respondents of this study were customers who had transacted at one of the fast food restaurants in Malang, with a sample size of 100 people selected through purposive sampling. Data were analysed using path analysis techniques. The results showed that customer experience has a significant effect on customer satisfaction (coefficient β = 0.682; p-value = 0.000) and customer loyalty (coefficient β = 0.295; p-value = 0.002). In addition, customer satisfaction is also shown to have a significant effect on customer loyalty (coefficient β = 0.488; p-value = 0.000). Based on these results, fast food restaurants are advised to improve service quality, products, and store atmosphere to support customer satisfaction and loyalty.